Classics In Political Economy - EN24 - 202101 - Awapara Franco, Omar (2021)
This course explores ideas in the history of economics and philosophy about the division of labor, the basis of social cooperation, views about wealth (what is it?) how it is created and distributed, and its relation to value and justice. We will start at the beginning: Plato's and Aristotle's views on economics and the division of labor. Along the way we will examine the views of, among others, St. Thomas Aquinas, John Locke, Francois Quesnay, Bernard Mandeville, David Hume, Adam Smith, Jeremy Bentham, Thomas Robert Malthus, David Ricardo, Nassau Senior, John Stuart Mill, Karl Marx, W.S. Jevons, Joseph Schumpeter and F.A. Hayek.